2009
DOI: 10.5194/acp-9-6633-2009
|View full text |Cite
|
Sign up to set email alerts
|

Mexico City aerosol analysis during MILAGRO using high resolution aerosol mass spectrometry at the urban supersite (T0) – Part 1: Fine particle composition and organic source apportionment

Abstract: Project Description and Overview: Objectives: Determining the overall impact of atmospheric aerosols on radiative balance requires knowledge of the relative amounts of scattering and absorbing aerosols, their distributions, and their chemical and optical properties. This proposal was a continuation of measurements of aerosol scattering and absorption begun in Mexico City in 2003 in collaboration with MCMA 2003 and continuing in the Atmospheric Science Program field study, Megacity Aerosol Experiment-Mexico Cit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

148
666
9
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 565 publications
(841 citation statements)
references
References 109 publications
148
666
9
3
Order By: Relevance
“…3), we therefore explore all solutions and use the criteria of finding physically meaningful factors to choose a good solution. Following the assumption that we will likely find the same factors from this dataset as Aiken et al (2009) reported for the HR-MS data in that 2-D factorization, we expect to need at least four factors in the solution. However, we also explore solutions with more factors in case new factors appear.…”
Section: Results From the 3-vector Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…3), we therefore explore all solutions and use the criteria of finding physically meaningful factors to choose a good solution. Following the assumption that we will likely find the same factors from this dataset as Aiken et al (2009) reported for the HR-MS data in that 2-D factorization, we expect to need at least four factors in the solution. However, we also explore solutions with more factors in case new factors appear.…”
Section: Results From the 3-vector Modelmentioning
confidence: 99%
“…During the campaign, size-resolved submicron aerosol composition was measured near downtown Mexico City by highresolution time-of-flight aerosol mass spectrometry (HRToF-AMS). Previous factor analysis of the bulk submicron organic composition dataset, i.e., without making use of the size-resolved data, identified contributions to the organic aerosol from HOA, BBOA, OOA, and a locally occurring organic aerosol (LOA, Aiken et al, 2009). The 3-D factorization techniques used in this study allow us to obtain robust estimates of the size distributions of these aerosol components and perhaps identify additional components.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, recent field studies in Mexico City (Molina et al, 2007 have shown that mobile sources emit abundant amounts of primary PM and that their emissions estimates in current official emissions inventories are highly uncertain (Aiken et al, 2009;Zavala et al, 2009a). Uncertainties in emissions inventories may arise when model-based techniques are used for the estimation of PM emissions from mobile sources due to propagations of uncertainties in: (1) the databases for inventorying and classifying the vehicle's activity levels, number and fuel characteristics, as well as roads type, driving modes, and ambient data representative of the local conditions; (2) the use of non-locally measured and model-based emissions factors.…”
Section: Introductionmentioning
confidence: 99%